The origin and evolution of the Menui Basin, part of the Matarombeo Terrain, Southeastern Arm of Sulawesi, Based on Geological and Geophysical Data - Samodra, Saptono Budi; Surjono, Sugeng Sapto; Amijaya, Donatus Hendra; Suryanto, Wiwit (Faculty of Geography, Universitas Gadjah Mada, 2025)
Menui Sub-basin is a part of Matarombeo terrain, located in south-east arm of Sulawesi Island – Indonesia. Matarombeo terrain geologically is bounded by Matano Fault, Lawanopo Fault, and Tolo Trust. Different from western part of Matarombeo Terrain that consist of Mountain, Menui Sub-basin is located at eastern part of Matarombeo Terrain, covered by sea water of Tolo Bay. The aim of this research is to interpreted basin formation and evolution of Menui Sub-basin, based on geomorphological and geological observation, further than stratigraphic and structural analysis. Research method included IFSAR image interpretation, geological field observation, and laboratory analysis such as petrography, paleontology, structural geology and sub surface analysis. Geologic and structural geology data were collected from surface mapping in land of Matarombeo, but sub-surface interpretation beneath Tolo bay were taken from gravity and seismic data. Stratigraphically, study area consist of Cretaceous – Oligocene ophiolite series which thrusted above Mesozoic sedimentary rocks from the continental crust origin. Unconformably above those two rock groups deposited molasse group on Miocene. The study area has been affected by three different tectonic stress phases. Formation and evolution of Menui Sub-Basin is characterized by several distinct events. The events begin from its history as part of Australia (pre-rifting sequence), the detachment from Australia (syn-rifting sequence), movement to its present location (syn-drifting sequence) and during and after the collision with SE Sulawesi (syn-orogen and post-orogen sequences).Received: 2025-11-24 Revised: 2025-12-13 Accepted: 2025-12-31 Published: 2025-12-31